1995
DOI: 10.1074/jbc.270.34.20073
|View full text |Cite
|
Sign up to set email alerts
|

G12 Requirement for Thrombin-stimulated Gene Expression and DNA Synthesis in 1321N1 Astrocytoma Cells

Abstract: Thrombin stimulation of 1321N1 astrocytoma cells leads to Ras-dependent AP-1-mediated transcriptional activation and to DNA replication. In contrast to what has been observed in most cell systems, in 1321N1 cells these responses are pertussis toxin-insensitive. The pertussis toxin-insensitive G-protein G12 has been implicated in cell growth and transformation in different cell systems. We have examined the potential role of this protein in AP-1-mediated transcriptional activation and DNA synthesis in 1321N1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 27 publications
2
98
0
1
Order By: Relevance
“…We have previously demonstrated that thrombin treatment induces Ras activation in 1321N1 cells and that the heterotrimeric G protein G 12 is required for thrombin-induced mitogenesis (LaMorte et al, 1993;Aragay et al, 1995). While expression of an activated form of Ga 12 can activate Ras , the mechanism of Ras activation by this PTX-insensitive G protein is unclear, particularly as the direct e ectors of Ga 12 are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that thrombin treatment induces Ras activation in 1321N1 cells and that the heterotrimeric G protein G 12 is required for thrombin-induced mitogenesis (LaMorte et al, 1993;Aragay et al, 1995). While expression of an activated form of Ga 12 can activate Ras , the mechanism of Ras activation by this PTX-insensitive G protein is unclear, particularly as the direct e ectors of Ga 12 are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that G 12 transduces thrombin's mitogenic signals in 1321N1 cells and that expression of the GTPase-de®cient Ga 12 Q229L results in Ras activation (Aragay et al, 1995;Collins et al, 1996). We hypothesized that Ga 12 may stimulate Ras through tyrosine kinase activation and Shc phosphorylation.…”
Section: G 12 Stimulates Shc Phosphorylationmentioning
confidence: 99%
See 3 more Smart Citations